Back analysis of a pillar monitoring experiment at 2.4 km depth in the Sudbury Basin, Canada. (May 2016) - Walton, G.; Diederichs, M.; Punkkinen, A.; Whitmore, J.
Abstract: In November 2013, a pillar monitoring and back analysis experiment was initiated on the 7910 level of the Creighton Mine, in Sudbury, Canada. An extensometer array was installed horizontally through the pillar to allow zones of brittle spalling damage and dilatancy in the granitic rockmass to be identified. To aid in the interpretation of the in-situ data, laboratory data were analyzed and a calibrated three-dimensional finite-difference model of the mining area was developed. Based on an interpretation of the available data and models, it was determined that following the onset of yield, pillar cohesion degrades more rapidly than pillar frictional strength increases. The overall rockmass strength remains relatively unchanged, however, due to dilation-induced confining stress increases. As the primary dilatancy of the pillar begins to decay and the pillar walls expand, the confinement in the pillar drops. This is followed by an increase in the vertical load sustained by the pillar as the effects of mobilizing friction strength begins to dominate the rockmass behavior. The relationships demonstrated between dilatancy, strength evolution, and stress path, have significant implications for support design and understanding rockburst mechanisms. Highlights: A mine-by experiment was conducted in a highly stressed environment. Ground movement during subsequent mining activities was measured. A back analysis was performed to calibrate a numerical model. The effect of dilatancy on pillar strength and stress evolution was examined.